2018
DOI: 10.1111/ene.13848
|View full text |Cite
|
Sign up to set email alerts
|

TTTCA repeat expansion causes familial cortical myoclonic tremor with epilepsy

Abstract: Background and purpose The aim was to investigate whether abnormal TTTTA and TTTCA repeat expansions in introns of SAMD12, TNRC6A and RAPGEF2 are involved in the pathogenesis of familial cortical myoclonic tremor with epilepsy (FCMTE). Methods Five families diagnosed with FCMTE were included in the current genetic analysis. Whole‐exome sequencing was performed in selected patients of each family. TTTTA and TTTCA expansions were examined by repeat‐primed polymerase chain reaction. The clinical features of FCMTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…A recent report of BAFME pedigree identified interindividual instability of the pentanucleotide repeats and inversely correlated with age at onset of myoclonic tremor and seizure (11). Our study confirmed the interindividual instability, but minimum repeat size estimated by RP-PCR shows no relation to the age of onset in this BAFME family.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A recent report of BAFME pedigree identified interindividual instability of the pentanucleotide repeats and inversely correlated with age at onset of myoclonic tremor and seizure (11). Our study confirmed the interindividual instability, but minimum repeat size estimated by RP-PCR shows no relation to the age of onset in this BAFME family.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, pentanucleotide expansions of intronic TTTCA and TTTTA were found to be involved in the pathogenesis of BAFME 1 in Japanese pedigrees regardless of the gene location (4). Three more recent reports also confirmed TTTCA pentanucleotide expansions in BAFME 1 families of another ethic background (9)(10)(11). Subsequently, TTTCA repeat insertions in an intron of YEATS2 in BAFME 4 was confirmed in a Thailand pedigree (7).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, the associations of the expanded dodecamer repeat from the cystatin B (CSTB) gene promoter with progressive myoclonus epilepsy (EPM1) [16][17][18] were identified. For instance, length polymorphisms of 5-HTTLPR and 5-HTTVNTR (VNTR-2, STin2) of the serotonin transporter gene (5-HTT) with susceptibility to temporal lobe epilepsy (TLE) [19,20], the monoamine oxidase A promoter variable number of tandem repeat (MAOA-uVNTR) with temporal lobe epilepsy with hippocampal sclerosis (TLE-HS) [21], and expansion of intronic pentanucleotide repeats of SAMD12, STARD7, YEATS2 and MARCH 6 genes with adult benign familial myoclonic epilepsy (BAFME) [22]. Those associations of tandem repeats with diseases may be explained by their participation in the regulation of gene expression [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the repeat expansion in intron four of SAMD12 was the most frequent and was observed in 48 out of 51 FCMTE families 9 . These findings were subsequently validated in additional Japanese and Chinese families with FCMTE 10–13 . Here, we present a large multigenerational Chinese family with more than twenty individuals with FCMTE symptoms from five generations that we have been studying for 23 years.…”
Section: Introductionmentioning
confidence: 71%
“…9 These findings were subsequently validated in additional Japanese and Chinese families with FCMTE. [10][11][12][13] Here, we present a large multigenerational Chinese family with more than twenty individuals with FCMTE symptoms from five generations that we have been studying for 23 years. Using a combination of the repeatprimed PCR, long-range PCR, and PacBio sequencing, we identified a 4.2-4.7 kb repeat with 549-603 copies of TTTTA and 287-343 copies of TTTCA repeat motifs in intron four of SAMD12 in affected individuals.…”
Section: Introductionmentioning
confidence: 99%